2001
DOI: 10.4049/jimmunol.166.6.3672
|View full text |Cite
|
Sign up to set email alerts
|

Functional Caspase-1 Is Required for Langerhans Cell Migration and Optimal Contact Sensitization in Mice

Abstract: Langerhans cell (LC) migration from epidermis to draining lymph node is a critical first step in cutaneous immune responses. Both TNF-α and IL-1β are important signals governing this process, but the potential regulatory role of IL-1α processing by caspase-1 is unknown. In wild-type (WT) mice, application of the contact allergens 2,4-dinitrofluorobenzine and oxazolone lead to a marked reduction in epidermal LC numbers, but in caspase-1-deficient mice this reduction was not observed. Moreover, although intrader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 30 publications
0
73
0
1
Order By: Relevance
“…Caspase-1 and IL-1b have been previously implicated in the sensitization phase. 91,92 Similarly, NALP3-deficient mice that receive cells from wild-type sensitized animals develop the T-cell dependent elicitor phase, suggesting that NALP3 is involved in the sensitization phase and may bridge the TNP-Cl stress signal with the activation of the adaptive immunity. A related agent 2,4-dinitrofluorobenzene that is able to induce contact hypersensitivity promotes the release of IL-1b via caspase-1 in a skin dendritic cell line suggesting that the inflammasome may directly detect such compounds.…”
Section: Nalp3 and Activation Of The Adaptive Immune Systemmentioning
confidence: 99%
“…Caspase-1 and IL-1b have been previously implicated in the sensitization phase. 91,92 Similarly, NALP3-deficient mice that receive cells from wild-type sensitized animals develop the T-cell dependent elicitor phase, suggesting that NALP3 is involved in the sensitization phase and may bridge the TNP-Cl stress signal with the activation of the adaptive immunity. A related agent 2,4-dinitrofluorobenzene that is able to induce contact hypersensitivity promotes the release of IL-1b via caspase-1 in a skin dendritic cell line suggesting that the inflammasome may directly detect such compounds.…”
Section: Nalp3 and Activation Of The Adaptive Immune Systemmentioning
confidence: 99%
“…Previous studies have shown that the greatest reduction in epidermal LCs occurs at 4 hours. 39,45 In this study, 4 hours after application of oxazolone there was an expected Figure 5A). In normal mice there was a significant decline in LC frequency in sensitized skin compared with vector-treated skin (from 836 Ϯ 107 LC/mm 2 to 535 Ϯ 71 LC/mm 2 ; P Ͻ .001; Student t test) ( Figure 5B).…”
Section: Diminished Migration Of Wasp-null Lcs After Contact Sensitizmentioning
confidence: 99%
“…The method of LC quantification followed has been described previously. 39 Briefly, ears were excised and split into dorsal and ventral halves using fine forceps. Dorsal halves were incubated in 0.02 M EDTA at 37°C for 90 minutes to allow separation of the epidermis and dermis.…”
Section: Oxazolone Sensitization and Immunohistochemical Staining Of mentioning
confidence: 99%
“…Epidermal sheets and epidermal single-cell suspensions were obtained as previously described (19,20). Cord blood was obtained following informed consent.…”
Section: Cell Preparationmentioning
confidence: 99%
“…Epidermal sheets were obtained as previously described (19) and were labeled with rat anti-mouse IA-IE-PE Ab (BD Pharmingen) (1/ 100 dilution) to detect LC. Samples were visualized by epifluorescent microscopy and images of six randomly chosen microscopic fields were acquired.…”
Section: Lc Countsmentioning
confidence: 99%